1989
DOI: 10.1073/pnas.86.8.2844
|View full text |Cite
|
Sign up to set email alerts
|

GLQ223: an inhibitor of human immunodeficiency virus replication in acutely and chronically infected cells of lymphocyte and mononuclear phagocyte lineage.

Abstract: GLQ223 is a highly purified, formulated preparation of trichosanthin, a 26-kDa plant-derived ribosome-inactivating protein with potent inhibitory activity against human immunodeficiency virus (HIV) in vitro. The compound produced concentration-dependent inhibition of HIV replication in acutely infected cultures of T-lymphoblastoid cells (VB cell line). Treatment with GLQ223 selectively reduced levels of detectable viral proteins compared to total cellular protein synthesis and produced a selective decrease in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
92
0
1

Year Published

1995
1995
2018
2018

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 277 publications
(93 citation statements)
references
References 19 publications
0
92
0
1
Order By: Relevance
“…These natural antioxidants have been strongly associated with reduced risk of chronic diseases, and age-related functional decline in addition to other health benefits [4] [5]. The medicinal importance of the plant also includes uses as a therapeutic agent for AIDS [6], as a tonic and in curing coughs while the seeds are used as purgative, anthelmintic and in the treatment of syphilis [7].…”
Section: Introductionmentioning
confidence: 99%
“…These natural antioxidants have been strongly associated with reduced risk of chronic diseases, and age-related functional decline in addition to other health benefits [4] [5]. The medicinal importance of the plant also includes uses as a therapeutic agent for AIDS [6], as a tonic and in curing coughs while the seeds are used as purgative, anthelmintic and in the treatment of syphilis [7].…”
Section: Introductionmentioning
confidence: 99%
“…In the late 1980s, TCS was the first RIP found to possess anti-HIV activity. It preferentially inhibited the replication of HIV-1 in both acutely infected T-lymphoblastoid cells and chronically infected macrophages in vitro [16]. Therefore, it is also a potential therapeutic agent for AIDS.…”
Section: Introductionmentioning
confidence: 99%
“…Clinically, it is used in China to terminate early and midtrimester pregnancies (8) and to treat trophoblastic tumors (9). In the late 1980s, studies showed TCS to be a potential therapeutic agent against HIV infection (10,11). In the early 1990s, TCS was used in the treatment of patients with AIDS or AIDS-related complex in phase I and II studies (12 -15).…”
Section: Introductionmentioning
confidence: 99%